Comparision study between convenstional method and mircrowave irradiation method to synthesize oxadiazole derivatives - K.Rama Devi; K.S.K. Rao Patnaik; D.Ashok; Raju Bathula; Satla Shobha Rani; B.Vasudha; Swathi Gopagoni (International Journal of Pharmacy and Analytical Research, 2022)
The survey of literature reveals that 1,3,4-oxadiazole moiety possesses a wide range of pharmacological activities such as antimicrobial, antimitotic, analgesic, antilieshmanial, antimycobacterial, antiinflamatory, antiinsecticidal, antitubercular and anti-HIV. Oxadiazole derivatives found to possess certain specific pharmacological activities. By taking the view in the mind we are prepared some oxadiazole derivatives by conventional and microwave irradiation method. In this work we compared the conventional and microwave irradiation methods.